The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/nu8090576
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Mouth Rinsing Enhances High Intensity Time Trial Performance Following Prolonged Cycling

Abstract: There is good evidence that mouth rinsing with carbohydrate (CHO) solutions can enhance endurance performance (≥30 min). The impact of a CHO mouth rinse on sprint performance has been less consistent, suggesting that CHO may confer benefits in conditions of ‘metabolic strain’. To test this hypothesis, the current study examined the impact of late-exercise mouth rinsing on sprint performance. Secondly, we investigated the effects of a protein mouth rinse (PRO) on performance. Eight trained male cyclists partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(77 reference statements)
2
13
1
Order By: Relevance
“…Thus, we associate it with carbohydrate depletion, which influences the individuals’ capacity to sustain free running. This result, extracted by our analysis, is related to other investigations such as the importance of R as a fitness indicator, even in untrained individuals ( Ramos-Jiménez et al, 2008 ), the metabolic role of R during exercise in trained athletes ( Goedecke et al, 2000 ), and carbohydrates’ role in helping athletes to improve performance ( Egan and D’Agostino, 2016 ; Luden et al, 2016 ). During tethered running, the eigenvalue metric reached its maximum for velocity in the Time Limit test.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, we associate it with carbohydrate depletion, which influences the individuals’ capacity to sustain free running. This result, extracted by our analysis, is related to other investigations such as the importance of R as a fitness indicator, even in untrained individuals ( Ramos-Jiménez et al, 2008 ), the metabolic role of R during exercise in trained athletes ( Goedecke et al, 2000 ), and carbohydrates’ role in helping athletes to improve performance ( Egan and D’Agostino, 2016 ; Luden et al, 2016 ). During tethered running, the eigenvalue metric reached its maximum for velocity in the Time Limit test.…”
Section: Discussionsupporting
confidence: 73%
“…Finally, magnitude based inferences have also revealed that CHO MR leads to a likely decrease in RPE for the same power output compared to PL. This result is very interesting since results are mixed and most studies have failed to observe benefits from CHO MR [ 9 , 44 , 75 , 76 , 77 ] and CAF MR [ 18 , 78 ] on perception of effort. Only a few studies have reported that CAF and CHO MR could lead to a decrease in RPE [ 25 , 26 , 27 ] suggesting that CHO and CAF MR induce a decrease in subjective perception of effort, allowing participants to produce more power with the same degree of discomfort.…”
Section: Discussionmentioning
confidence: 89%
“…Effect sizes for GLM were calculated using partial eta square ( ɳ p 2 ). Secondly, to specifically test effects of nutritional supplements and RPE, we also reported probabilistic magnitude-based inferences about all the variables using methods described by Hopkins et al [ 43 ] which has been applied in several recent nutritional studies [ 21 , 44 , 45 ]. Data were log-transformed prior to analyses to reduce bias arising from non-uniformity of error.…”
Section: Methodsmentioning
confidence: 99%
“…mean and standard deviation or standard error). The following studies were excluded from the analysis; Beaven et al (3) because raw data was not available for the placebo condition (an attempt was made to contact the author), Rollo et al (39) because the performance outcome was self-selected running speed which is not in itself a performance measure per se that could be compared to the outcomes of other studies in the same sub-analysis, Rollo et al (40) because CMR was not compared to a placebo mouth rinse, Rollo et al (review) because it was a review article, and three studies were excluded because the mouth rinse efficacy could have been influenced by a prior exercise (1,30,36). An overview of the search strategy is outlined in Fig 1. The effectiveness of the mouth rinsing was quantified by determining the effect size for each variable, which can be categorised as small (0.2), moderate (0.5) or high (0.8).…”
Section: Methodsmentioning
confidence: 99%